Novel localization of folate transport systems in the murine central nervous system - Vishal Sangha; Md. Tozammel Hoque; Jeffrey T. Henderson; Reina Bendayan (Fluids and Barriers of the CNS, 2022)
Abstract Background Folates are a family of B9 vitamins that serve as one-carbon donors critical to biosynthetic processes required for the development and function of the central nervous system (CNS) in mammals. Folate transport is mediated by three highly specific systems: (1) folate receptor alpha (FRα; FOLR1/Folr1), (2) the reduced folate-carrier (RFC; SLC19A1/Slc19a1) and (3) the proton-coupled folate transporter (PCFT; SLC46A1/Slc46a1). Folate transport into and out of the CNS occurs at the blood–cerebrospinal fluid barrier (BCSFB), mediated by FRα and PCFT. Impairment of folate transport at the BCSFB results in cerebral folate deficiency in infants characterized by severe neurological deficiencies and seizures. In contrast to the BCSFB, CNS folate transport at other brain barriers and brain parenchymal cells has not been extensively investigated. The aim of this study is to characterize folate transport systems in the murine CNS at several known barriers encompassing the BCSFB, arachnoid barrier (AB), blood–brain barrier (BBB) and parenchymal cells (astrocytes, microglia, neurons). Methods Applying immunohistochemistry, localization of folate transport systems (RFC, PCFT, FRα) was examined at CNS barriers and parenchymal sites in wildtype (C57BL6/N) mice. Subcellular localization of the folate transport systems was further assessed in an in vitro model of the mouse AB. Gene and protein expression was analyzed in several in vitro models of brain barriers and parenchyma by qPCR and western blot analysis. Results RFC, PCFT, and FRα expression was localized within the BCSFB and BBB consistent with previous reports. Only RFC and PCFT expression was detected at the AB. Varied levels of RFC and PCFT expression were detected in neuronal and glial cells. Conclusions Localization of RFC and PCFT within the AB, described here for the first time, suggest that AB may contribute to folate transport between the peripheral circulation and the CSF. RFC and PCFT expression observed in astrocytes and microglia is consistent with the role that one or both of these transporters may play in delivering folates into cells within brain parenchyma. These studies provide insights into mechanisms of folate transport in the CNS and may enhance our understanding of the critical role folates play in neurodevelopment and in the development of novel treatment strategies for disorders of brain folate deficiency due to impaired transporter function.